Benefits and Process of Providing Peer Support for Pediatric Burn Survivors and Caregivers during Inpatient and Outpatient Phases of Recovery - Rosenberg, Marta; Rodriguez, Robert; Grant, Staci; Miguel, Alicia San; Lee, Jong O.; Rosenberg, Laura (Seminars in Plastic Surgery, 2024)
The World Health Organization reveals that pediatric burns represent a large portion of burns globally (61). Increases in survival rates have guided clinical and research focus on physical, psychological, and social outcomes. Research on other childhood illnesses has shown the efficacy of social support throughout recovery. In the pediatric burn literature, studies have shown the efficacy of burn camps for promoting positive interactions among survivors, learning coping skills, and facilitating socialization and reintegration. However, few studies have focused on the benefits of peer support for pediatric burn survivors and their caregivers in the inpatient and outpatient phases of recovery. This descriptive paper identifies options for building resilience for pediatric burn survivors through peer support in the inpatient and outpatient phases of recovery. The authors discuss options for providing peer support during the coronavirus disease 2019 pandemic on the pediatric intensive care unit, general pediatric floor, and outpatient setting.
Keywords: pediatric; burns; peer support; resilience; interdisciplinary